Anaesthesia recommendations for patients suffering from Osteopetrosis - Ozer, Ayse Belin; Farfan, Miguel; Lezot, Frederic; Prottengeier, Johannes (Aktiv Druck & Verlag Gmbh, 2017)
Osteopetrosis is a rare disease caused by the failure of osteoclast function and impaired bone resorption. Marrow cavities will be filled with new endochondral bone from overwhelming osteoblast activity, leading to increased bone density, but decreased stability. Loss of haematopoieticly active bone marrow leads to pancytopenia and the re-activation of extra-medullary haematopoiesis. Alterations in bone mass, function as well as inner and outer form will cause pathologic fractures, mass effects, such as tissue compression, and can lead to pathognomonic, especially facial features. Alterations to airway, cervical spine and thoracic wall are of special interest to anaesthesia. Secondary disorders comprise anaemia, bleeding disorders, immunodeficiency, hepatosplenomegaly, hypocalcaemia, hyper-phospataemia and renal acidosis. Clinical severance is a result of different combinations of gene dysfunctions related to osteoclast physiology. Despite of rather heterogeneous genetic arrays, the classification of osteopetrosis still relies on inheritance patterns. Autosomal dominant osteopetrosis is clinically mild, and sometimes not diagnosed until adulthood. It has an incidence of 5 in every 100,000 births, usually solely presents with pathologic fractures and comes with normal life expectancy. The autosomal recessive variant of osteopetrosis is more severe, becomes symptomatic early in infancy and childhood, and has an incidence rate of 1 in every 250,000 births. In its most severe phenotype of malignant infantile osteopetrosis, life expectancy is reduced to adolescence, and the most common causes of death are anaemia, bleeding and septicemia. Calcitriol, steroids and interferon-gamma may be somewhat beneficial, but haematopoietic stem-cell transplantation offers the most effective treatment option available up to date.
Keywords: Marble bone disease; Albers-Schonberg disease; osteosclerosis; fragilitas generalisata; osteopetrosis generalisata